PENCEGAHAN KECURANGAN PENGELOLAAN DANA DESA OLEH APARAT DESA DI KABUPATEN KULONPROGO - nurna pratiwi; Anik Puji Handayani (Universitas Sarjanawiyata Tamansiswa, 2023)
Villages are given sources of funds and authority to manage the potential of the village government in order to improve the economy and welfare of the village community. Each village receives a very large village fund budget, therefore good village financial management is needed to minimize fraud. So that the purpose of this research is to determine the influence of competence, morality, suitability of compensation and the village financial system on the prevention of fraud in village fund management in Kulonprogo Regency. This research uses a survey method with a quantitative approach. The data source used is primary data. The sampling technique uses purposive sampling. Data analysis techniques use multiple regression analysis with the help of SPSS software version 21. The results of this study are competence, morality, suitability of compensation and the village financial system have a significant positive effect on the prevention of fraud in village fund management.